Effects of Cardiovascular Interval Training in Healthy Elderly Subjects: A Systematic Review - Sant'Ana, Leandro de Oliveira; Machado, Sérgio; Ribeiro, Aline Aparecida de Souza; Reis, Natália Rodrigues dos; Campos, Yuri de Almeida Costa; Silva, João Guilherme Vieira da; Scartoni, Fabiana Rodrigues; Brown, Amanda Fernandes; Monteiro, Estêvão Rios; Novaes, Jefferson da Silva; Vianna, Jeferson Macedo; Budde, Henning (Frontiers in Physiology, 2020)
The aim of this present review is to demonstrate the effects of cardiovascular interval training (IT) on effects healthy elderly subjects. We used the recommendations of the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. The following variables were observed: resting heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MBP), heart rate variability (HRV), baroreflex activity (BA) and maximal oxygen uptake (VO2max). The studies were searched in the MedLine, PubMed and Sport Discus databases considering publications between 1990 and 2019. To find the studies, the keywords were used Interval and Elderly Training or Interval Training and Baroreflex Sensing or Interval Training and Aging and Pressure Arterial and Blood Pressure Training or Interval Training and Variation in Aging and Heart Rate or Interval Training and Sensitivity to the Elderly and Baroreflex or Interval Training and Variability in the Elderly and Heart Rate. The systematic search identified 1.140 hits. The analysis of the study was performed through a critical review of the content. 1,140 articles were identified. Of these, 1,108 articles were excluded by checking the articles and abstracts. Finally, 32 studies were selected for full reading where 26 studies were eliminated because they did not contain a methodology according to the purpose of this review. Thus, 6 studies were included for the final analysis. The PEDro score was used for analyzing the study quality and founded 4,8 ± 1,3 points (range: 3-6). Positive results were found with the different IT protocols in the observed variables. Results show that IT protocols can be an efficient method for functional improvement of cardiovascular and cardiorespiratory variables in healthy elderly, especially HRR, SBP, DBP, MAP, HRV, BA and VO2max. However, this method can be included in the prescription of aerobic training for the elderly to obtain conditional improvements in the cardiovascular system, thus being an important clinical intervention for the public.